Biosorption of Ni(II), Cr(III), and Co(II) from Solutions Using Acalypha hispida Leaf: Kinetics, Equilibrium, and Thermodynamics - Adesola Babarinde; J. Oyebamiji Babalola; John Adegoke; Adebola O. Osundeko; Susan Olasehinde; Adetayo Omodehin; Emmanuel Nurhe (Journal of Chemistry)
Biosorption studies were conducted to study the removal of Ni(II), Cr(III), and Co(II) from aqueous solution of Acalypha hispida leaf. The FTIR spectral characteristics of Acalypha hispida leaf revealed the presence of ioniazable groups that could participate in the binding of metal ions in solution. The kinetic, equilibrium, and thermodynamic studies of the biosorption of the metal ions were investigated using various physicochemical parameters; each parameter was found to affect the biosorption process. The kinetic studies showed that the biosorption process was best represented by pseudo-second-order kinetics among four kinetic models tested. Equilibrium data were better represented by Freundlich isotherm among Langmuir and Freundlich adsorption isotherms. The study on the effect of dosage showed that the dosage of the biomass significantly affected the uptake of the metal ions from solution. Thermodynamic parameters such as standard Gibbs-free energy (), standard enthalpy (), standard entropy (), and the activation energy were calculated. The order of spontaneity of the biosorption process was found to be Cr(III) > Ni(II) > Co(II). The activation energy for the biosorption of each of the metal ions was less than 42 kJmol−1 at 323 K indicating that each was a diffusion-controlled process.